An Analysis of Anthropometric Indicators and Modifiable Lifestyle Parameters Associated with Hypertensive Nephropathy - Christiana Aryee; William K. B. A. Owiredu; James Osei-Yeboah; Ellis Owusu-Dabo; Edwin F. Laing; Isaac K. Owusu (International Journal of Hypertension)
The surge in prevalence of chronic noncommunicable diseases like hypertension and chronic kidney disease has been linked with modifiable lifestyle practices and increased body fat. This study sought to compare the association between different modifiable lifestyle practices, adiposity indices, renal function parameters, and hypertension as well as the predictive implications for levels of these parameters in target cardiac organ damage among an urban Ghanaian hypertensive population. Using a hospital-based case-control study design, 241 Ghanaian indigenes from the Kumasi metropolis were recruited for this study. The case group was made up of 180 hypertensives and 61 normotensives served as controls. In addition to sociodemographic data, standard haemodynamic, anthropometric, renal function, and cardiac organ damage assessments were done. The prevalence of chronic kidney disease (CKD) ranged from 13.3% to 16.6% depending on the equation used in estimating the glomerular filtration rate (eGFR). Percentage cluster distribution by chronic kidney disease was observed to be significantly tilted toward the upper quartiles (3rd and 4th) of the haemodynamic parameters measured. Chronic kidney disease was significantly higher among self-reported smokers and alcoholic hypertensives. In this urban population, adiposity was associated with hypertension and renal insufficiency. Chronic kidney disease was associated with hypertension and cardiac abnormalities.